Study on the Root Crack Propagation Characteristics and Residual Life of Case-hardened Gears - Wu Luji; Yang Shihao; Yang Linjie; Li Youhua (Jixie chuandong)
In order to study the influence of tooth root cracks on the fatigue life of case-hardened gears, taking an involute case-hardened gear as the research object, the mechanism of the tooth root fatigue crack growth is analyzed based on the fracture mechanics method and fatigue crack growth theory. The residual life analysis model of the tooth root crack propagation for case-hardened gears is established, considering the influence of load, initial crack size and initial crack location, etc. The evolution of stress intensity factor and crack propagation mechanism at different root crack propagation stages is studied. According to the bending fatigue test data of an involute case-hardened gear pair, the calculation model is analyzed and verified, and the accuracy of the model is proved. The results indicate that, compared with type Ⅱ and type Ⅲ, type Ⅰ stress intensity factor is the highest, which gradually decreases from the tooth surface to the direction of crack depth. With the increase of factors such as load, crack length, crack width, and initial crack distance from the center position of the tooth width, the residual life of crack propagation decreases accordingly.